Religious Education Guidance in Improving the Spirituality of Victims of Drug Abuse - Pratiwi, Rahmi; Mukhtaruddin, Mukhtaruddin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to explain the implementation of religious education guidance in improving spirituality at the Bhayangkara Indonesia Narcotics Abuse Prevention Rehabilitation Institute (LRPPN). This research is qualitative with a case study research approach. The research subjects were religious education guidance officers and clients at the Bhayangkara Indonesia Narcotics Abuse Prevention Rehabilitation Institute (LRPPN)—data collection methods using interviews, observation, and documentation. Data analysis is done through data reduction, presentation, conclusion drawing, and verification. The results showed that religious education guidance is very important to be given to clients who are undergoing drug rehabilitation. The implementation of religious education guidance provided to clients at the Bhayangkara Indonesia Drug Abuse Prevention Rehabilitation Institute (LRPPN) is in the form of mandatory 5-time prayer activities, Tahajud sunnah prayers, Duha, and repentance. Salim with the recitation of fadilah-fadilah with four book guidelines, morning & evening zikr, Muzakarah Adab, Tajwid, and Religy Group. Through the religious education guidance at the Bhayangkara Indonesia Drug Abuse Prevention Rehabilitation Institute (LRPPN), clients get many benefits that can be applied in the family and community environment after the client leaves the Rehabilitation Institution.